2022
DOI: 10.3390/app12199466
|View full text |Cite
|
Sign up to set email alerts
|

For Patients with Stroke, Balance Ability Affects the Leg Extension Angle on the Affected Side

Abstract: In stroke patients, the impact of lower limb physical functions on the leg extension angle remains unclear. We set out to reveal the physical impairments of the affected side in such patients that were associated with leg extension angle during gait. Twenty-six stroke patients walked for 16 m at a spontaneous speed. During walking, the leg extension angle and the increment of velocity during late stance, as an indicator of propulsion, were measured by inertial measurement units. The Berg balance scale (BBS), F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Moreover, the cut-off BBS score of 29 on admission predicted that an individual would go on to achieve community walking speed (n = 123, area under the curve = 0.88, 95% confidence interval [CI] 0.81–0.95), and the cut-off score of 12 predicted a non-ambulator to regain unassisted ambulation (n = 84, AUC 0.73, 95% CI 0.62–0.84) 21 . A recent study found that balance ability, as measured by the BBS, was a significant predictor of affected leg extension angle during gait in stroke patients (p < 0.001) 22 . They also suggested that increasing balance ability is useful in increasing leg extension angle during walking and may be effective in improving walking speed 22 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the cut-off BBS score of 29 on admission predicted that an individual would go on to achieve community walking speed (n = 123, area under the curve = 0.88, 95% confidence interval [CI] 0.81–0.95), and the cut-off score of 12 predicted a non-ambulator to regain unassisted ambulation (n = 84, AUC 0.73, 95% CI 0.62–0.84) 21 . A recent study found that balance ability, as measured by the BBS, was a significant predictor of affected leg extension angle during gait in stroke patients (p < 0.001) 22 . They also suggested that increasing balance ability is useful in increasing leg extension angle during walking and may be effective in improving walking speed 22 .…”
Section: Discussionmentioning
confidence: 98%
“…A recent study found that balance ability, as measured by the BBS, was a significant predictor of affected leg extension angle during gait in stroke patients (p < 0.001) 22 . They also suggested that increasing balance ability is useful in increasing leg extension angle during walking and may be effective in improving walking speed 22 . Therefore, gait performance with compensatory adaptations of patients with strokes was associated with balance deficit and the relationship of these factors in the physical functioning of these patients requires consideration.…”
Section: Discussionmentioning
confidence: 98%